Protein phosphatase inhibitors: a distillation of cell signaling research and water toxicology - MacKintosh, Carol (Henry Stewart Talks, 2010)
Toxic inhibitors of protein PPP family serine/threonine phosphatases, Use of these compounds to characterize the functions and structures of PPP enzymes, The natural ecological contexts of the toxins, Okadaic acid and the shellfish industry, Microcystin in freshwater cyanobacteria, Contrasts in how microcystin in regarded legally by the security and water industries, Attempts to understand global trends in microcystin